KERJASAMA INDUSTRI PERTAHANAN INDONESIA-JERMAN DAN TRANSFER OF TECHNOLOGY (TOT) TANK LEOPARD PERIODE TAHUN 2012-2014 - Alfani Ekaditri Mardiah, - (2018)
The research title is "The Cooperation of Defense Industry of Indonesia-Germany and Transfer Of Technology (TOT) Leopard Tank Period 2012 - 2014". Data will be analyzed using Bilateral Relation Theory, National Concept of Interest, Defense Industry Concept, and Transfer Technology Concepts. The approach of this research is qualitative. The type of research used is applied and descriptive. The data sources used are primary and secondary data from interviews, library study and audio-visual recording, as well as data on consumption, conservation, availability and production, and Indonesian military training data with Germany from the Indonesian Ministry of Defense. Indonesia has no Main Battle Tank (MBT) as the most powerful cavalry. The condition of Defense System Primary Tools belonging to the Armed Forces which is in a state of decent use is only 60%. The remaining 40% of Defense System Primary Tools still have to be repaired to be suitable for use. The Leopard MBT procurement effort for Indonesia through Germany also has the power of Pull. Based on data analysis conducted, it can be concluded that by having Leopard Revolution MBT then Indonesia, especially Army now has Defense System Primary Tools that able to balance ownership of MBT neighboring countries either Australia, Singapore or Malaysia. In particular, the TNI Army's MBT is superior to firing and destruction technology in the event of an inter- regional MBT war. Here is the great value of MBT for a country to have a bargaining position against another country.